Single-Channel Seismic Images from the Caribbean Sea and Western North Atlantic Ocean acquired during the R/V Robert D. Conrad expedition RC1003 (1965) (IEDA: Marine-Geo Digital Library, 2004)
This data set was acquired with the LDEO Single-Channel Seismic system during R/V Robert D. Conrad expedition RC1003 conducted in 1965 (Chief Scientist: Dr. Robert Wall). These data files are of JPEG format and include Single-Channel Reflection Seismic images that have not been processed after acquisition.